Elementary Equivalence of Linear Groups Over Graded Rings With Finite Number of Central Idempotents - Bunina, E. I.; Mikhalev, A. V. (Sarajevo Journal of Mathematics, 2024)
In this paper we prove the criterion of elementary equivalence of linear groups over graded rings with finite number of central idempotents from the 0-component, when grading is partially included in the group language. * This paper was presented at the International Scientific Conference Graded structures in algebra and their applications, dedicated to the memory of Prof. Marc Krasner, IUCDubrovnik, Croatia, September, 22-24, 2016.